Dual‐band circular polarisation generation technique with the miniaturisation of a rectangular dielectric resonator antenna. Issue 10 (10th May 2019) - Gotra, Shailza; Varshney, Gaurav; Yaduvanshi, Rajveer Singh; Pandey, Vinay Shankar
Abstract : A technique is proposed to obtain the dual‐band circularly polarised (CP) response along with the miniaturisation of a singly fed rectangular dielectric resonator (DR) antenna. The miniaturised response is obtained by applying the metallic strips on the sidewalls of the DR. The specific format of the applied metallic strips excites the orthogonal degenerate modes. Thus, a dual‐band CP response is obtained along with the miniaturisation of antenna. The proposed antenna is designed to obtain the small frequency ratio. The frequency ratio can also be tuned by changing the surface area of the applied metallic strips.